Integrated approach of remote sensing and micro-sensor technology for estimating evapotranspiration in Cyprus - Hadjimitsis, Diofantos G.; Papadavid, George (My University, 2010)
The objective of this research project is to describe and apply a procedure for monitoring and improving the performance of on-demand irrigation networks, based on the integration of remote sensing techniques and simulation modeling of irrigation water in Cyprus, which is facing a severe drought in the last five years. Multi-spectral satellite images are used to infer crop potential evapotranspiration, which is the main input for water balance simulations. The need for estimating ET in Cyprus is imposed in order to determine the exact quantity of irrigated water needed for each specific crop. The overuse of water for irrigation has resulted in eliminating the water resources in the whole island. The determination of ET for irrigation purposes will be used as a vital tool for supporting the decision-making process in the management of water resources, on a technocratic level, and on the other hand will have a positive effect on the rest of water resources of Cyprus. The integrated method applied, consisting of Remote Sensing techniques and micro-sensor technology, has shown that it can be a useful tool in the hands of agri-policy makers for sustainable irrigation.
Keywords: Remote sensing; Irrigation management; Wireless sensors; Sustainability